Insecticidal efficacy of non-Bt bacterial strains against diamondback moth, Plutella xylostella (L.) - Chem, Chanchao; Eslamloo, Ghazaleh; Ito, Tsukasa (Frontiers in Sustainable Food Systems, 2025)
The diamondback moth (Plutella xylostella L.), a major global pest of cruciferous vegetables, has resisted conventional insecticides, necessitating novel pest control strategies. In this study, we evaluated four non-Bt bacterial strains—Mesobacillus thioparans CC8, Bacillus mobilis CC13, Bacillus subtilis CC18, Chromobacterium rhizoryzae 4C2, and the effectiveness of bacterial consortia against P. xylostella L. larvae. The extracellular hemolysins and insecticidal activity utilizing the leaf-dip method were investigated. The effect of cell concentration, larval size, and exposure methods on insecticidal efficacy were examined. The fecal pellet examination was used to evaluate the presence of microbial communities, while scanning electron microscopy assessed gut damage. The findings demonstrated 100% larval mortality within 48 h of exposure, with the artificial selection, comprising four non-Bt bacterial strains, exhibiting enhanced efficacy compared to individual applications. Utilizing second-instar larvae with precisely dose-dependent cell densities increased mortality. Both leaf-dip and direct-spray application methods showed comparable efficacy, offering flexibility for practical applications. The target insecticidal bacteria were detected in the larval fecal microbiota, while the larva’s external features showed damage after exposure. This study highlights the potential of non-Bt insecticidal bacteria as an alternative strategy for managing P. xylostella L., contributing to the development of sustainable pest management solutions.